Disparity in Supreme Court Decisions and Medan Religious Court Decisions Regarding the Determination of Heirs - Syam, Syafruddin; Zahara, Fatimah; Pulungan, Madinah (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
The Supreme Court, through Decision Number 485 K/Ag/2013, issued a decision regarding determining the inheritance rights of non-Muslim heirs through the 'aṣabah sababiyah route. The legal basis regarding 'aṣabah sababiyah is not contained in the marriage law or the compilation of Islamic law. In its decision, the Supreme Court referred to the 'aṣabah sababiyah theory of Egyptian inheritance law. This decision is a legal effort based on the decision of the Medan Religious Court Number 751/Pdt.G/2011/PA.MDN, which stated that, in inheritance law, the number of ulama agreed to require that heirs and heirs must have the same religion, namely Islam. This problem is interesting to study in more depth through the views of the Medan Religious Court judges and analyze based on a progressive legal perspective. This research is empirical legal research with a qualitative approach, and data collection in this research uses observation, interview techniques, and then analysis. This research found that 'aṣabah sababiyah is an asabah in the class of heirs, which occurs because of freeing both male and female slaves. The views of the Medan Religious Court judges regarding Supreme Court decision Number 485 K/AG/2013 concerning the Determination of the Heirs of 'Ashabah Sababiyah are in two groups, namely accepting the decision and rejecting the decision. If the disparity in the decisions of the Supreme Court and the Medan Religious Court in determining heirs of different religions is viewed based on progressive law, then Supreme Court Decision Number 485 K/AG/2013 is closer to the value of legal progressivity because one form of application of progressive law by judges is to realize social justice through the method of legal discovery by placing social justice in society above statutory regulations.